2016
DOI: 10.1021/jacs.6b00631
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Stabilized Silacyclobutanone: A Precursor of 1-Silaketene via Retro-[2 + 2]-Cycloaddition Reaction at Room Temperature

Abstract: The synthesis of donor-stabilized silacyclobutanone 2 was successfully realized by the reaction of silacyclopropylidene 1 with benzaldehyde in the presence of a Lewis acid catalyst. Of particular interest, silacyclobutanone 2 evolves at room temperature via a retro-[2 + 2]-cycloaddition reaction, leading to an original NHC-stabilized 1-silaketene 4 and cis-stilbene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Complex 8 is sufficiently stable to be isolated as yellow crystals from a toluene solution (yield: 69 %), and it was fully characterized by NMR spectroscopy as well as by X‐ray diffraction analysis (Figure ) . The structure of 8 is similar to that of previously reported NHC‐stabilized 1‐silaketene . Of particular interest, the formation of 8 can be explained by an intramolecular cross‐metathesis reaction involving the silaketene functionality and the vinyl fragment of transient 1‐silaketene 2‐Py .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Complex 8 is sufficiently stable to be isolated as yellow crystals from a toluene solution (yield: 69 %), and it was fully characterized by NMR spectroscopy as well as by X‐ray diffraction analysis (Figure ) . The structure of 8 is similar to that of previously reported NHC‐stabilized 1‐silaketene . Of particular interest, the formation of 8 can be explained by an intramolecular cross‐metathesis reaction involving the silaketene functionality and the vinyl fragment of transient 1‐silaketene 2‐Py .…”
Section: Resultssupporting
confidence: 81%
“…Since the discovery of efficient methods to stabilize silanones by coordination of donor/acceptor ( VI ) or donor ligands ( VII ) by Driess et al., remarkable progress has been made in silanone chemistry . We have recently described the synthesis of a donor‐stabilized silacyclobutanone IV , which evolves at room temperature through a [2+2] cycloreversion, leading to a donor‐stabilized 1‐silaketene V (type IX ) and cis ‐stilbene, similar to the “Chauvin intermediate” metallacycle I (Figure ) . However, the irreversible dimerization of 1‐silaketene V via the silanone to afford a thermally stable cyclic siloxane, prevents any application of this unique phenomenon for metal‐free olefin metathesis.…”
Section: Introductionmentioning
confidence: 99%
“…Them olecular structure of 3 reveals at rigonal planar geometry around the boron atom (sum of angles at B = 359.38 8;F igure 1). [11b] Thee xceptionally strong p-back donation from the three-coordinate Ba tom to the s* P-N orbitals induces abnormally elongated PÀN2 and PÀN3 bonds (1.7595(6) and 1.7290(7) )c ompared to those observed in related phosphonium ylides, [24] and phosphanylidene-phosphoranes [10] (1.674-1.681 ). Indeed, this bond is much longer than those observed for other borylene complexes with cyclic CAACs( 1.462-1.518 ) [15] or oxazoli-2-ylidenes (1.496-1.511 ) [17] ligands, presenting as ubstantial BÀCm ultiple-bond character.…”
mentioning
confidence: 99%
“…[4] Silanones present as trongly polarized Si=Od ouble bond (Si d+ ÀO dÀ )w ith ac onsiderably large bond energy difference between SiO-p and SiO-s bonds, [5] and therefore,t hey easily oligomerize to give polysiloxanes. [7][8][9][10][11] Nevertheless,t he synthesis of stable threecoordinate silanone derivatives remains ad ifficult task, although the heavier analogue germanone III,well kinetically stabilized by bulky aryl substituents,h as been isolated by Matsuo/Tamao et al [12] At present only three examples are reported:1 )the transition-metal-substituted silanone IV, isolated at RT by Filippou et al, [13] 2) the cyclic dialkylsilanone V,c haracterized in situ at À80 8 8Cb yt he group of Iwamoto, [14] and 3) the relatively persistent (amino)-(ylide)silanones VI,r eported by us. [7][8][9][10][11] Nevertheless,t he synthesis of stable threecoordinate silanone derivatives remains ad ifficult task, although the heavier analogue germanone III,well kinetically stabilized by bulky aryl substituents,h as been isolated by Matsuo/Tamao et al [12] At present only three examples are reported:1 )the transition-metal-substituted silanone IV, isolated at RT by Filippou et al, [13] 2) the cyclic dialkylsilanone V,c haracterized in situ at À80 8 8Cb yt he group of Iwamoto, [14] and 3) the relatively persistent (amino)-(ylide)silanones VI,r eported by us.…”
mentioning
confidence: 99%
“…[6] Recently,e asy-to-handle silanones stabilized as donor-acceptor or donor complexes,h ave been reported. [7][8][9][10][11] Nevertheless,t he synthesis of stable threecoordinate silanone derivatives remains ad ifficult task, although the heavier analogue germanone III,well kinetically stabilized by bulky aryl substituents,h as been isolated by Matsuo/Tamao et al [12] At present only three examples are reported:1 )the transition-metal-substituted silanone IV, isolated at RT by Filippou et al, [13] 2) the cyclic dialkylsilanone V,c haracterized in situ at À80 8 8Cb yt he group of Iwamoto, [14] and 3) the relatively persistent (amino)-(ylide)silanones VI,r eported by us. [15] Therefore,t heir synthetic use is still limited because of the scarcity and limited lifetime (0.5-5 h, at RT for VI).…”
mentioning
confidence: 99%